Trials of (Alleged) Terrorists by Military Tribunals: Effective or Not? - Borch, Fred L. (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2026)
After al Qaeda’s September 11, 2001 attacks, U.S. President George Bush decided that those responsible – and other terrorists – should be prosecuted at military tribunals rather than in civilian courts. This article examines the wisdom of this decision and concludes that the use of military tribunals to prosecute alleged terrorists has not been effective but rather been a failure.